PENGEMBANGAN ASSESSMENT FOR LEARNING DALAM PRAKTIK PEMESINAN DI SMK SESUAI KURIKULUM 2013 - Endri Triwiyono (Jurnal Taman Vokasi, 2017)
This study aims to determine the development of assessment for learning tools on learning machining practices in VHS. This development research uses 3 stages: development, limited testing phase, and expanded testing stage. Research subjects were students and teachers of machining techniques VHS 2 Depok Sleman. Data collection using interviews, documentation, questionnaire questionnaires, field notes, observation sheets, product assessment sheets and student responses. Data analysis technique using descriptive analysis with rating method. The result of this research is assessment apparatus assessment apparatus developed successfully with characteristic of device consisted of process and product valuation device. Information on the results of the assessment is accurate information on student work process, product quality and overall result of practice assessment to know student achievement and as formative feedback with "good" rating level and can be applied at VHS majoring in machining technique.